Exotic pine plantations vs. native forests in northern Patagonia: Comparing growth patterns and climate change vulnerability - Reiter, Ernesto Juan (2025)
The area planted with exotic conifers has rapidly increased between the 1970s and 2000s in northern Argentinian Patagonia, replacing in many cases native Nothofagus and Austrocedrus forests. Direct comparisons between pine plantations and native forests with respect to growth patterns, productivity and climate vulnerability are lacking so far. Here, we explore differences in radial growth, climate sensitivity of growth and stomatal regulation between planted exotic (Pinus ponderosa, P. contorta, P. radiata) and neighboring even-aged native stands (Austrocedrus chilensis, Nothofagus dombeyi) during the stem-exclusion phase (first 32 years) using dendrochronology and stable isotope analysis of stem wood. While all Pinus stands reached maximum basal area increment (BAI) earlier than the native species, Nothofagus dombeyi was as productive as Pinus radiata, the most productive exotic conifer. The main climatic growth constraints were in all five species rainfall deficits and elevated temperatures in late spring/summer, with the most productive species being more sensitive to climate. Stem wood Δ¹³C and δ18O signatures suggest higher stomatal conductance and transpiration losses of the three exotic Pinus species and a recent transpiration increase compared to the native species with an apparently more conservative water use. Our results show that introduced Pinus species are not necessarily more productive than native tree species, and their growth may be more vulnerable to climate warming. Since all planted Pinus species are invasive in the region and are increasing the fire risk, it is advised in the face of climate change to preferably plant native tree species, where possible, and to reduce the area of conifer plantations.